Adsorptive Removal of Reactive Black 5 from Aqueous Solution using Chitin Prepared from Shrimp Shells - Begum, Hosne Ara; Mondal, Ajoy Kanti; Muslim, Tanvir (Bangladesh Pharmaceutical Journal, 2012)
The utilization of chitin as adsorbent for the removal of Reactive Black 5 (RB5) from aqueous solution was investigated. Chitin was prepared from shrimp shells using conventional method. Prepared chitin was characterized by FT-IR spectral and thermogravimetric analysis. Batch adsorption experiments were carried out as a function of contact time, initial concentration of RB5 solution, temperature and pH of the solution. The amount of adsorption of RB5 from aqueous solution on chitin increased with the increase of initial concentration of RB5 solution and temperature of the solution. The equilibrium adsorption data were fitted to the Langmuir and Freunlich isotherms. The best result was achieved with Langmuir isotherm model. The thermodynamics of reactive dye by chitin indicated its spontaneous and endothermic nature. The kinetic of the sorption was analysed using the pseudo firstorder and second-order kinetic models. The data showed that the pseudo second-order equation was the more appropriate. The experimental data showed that the adsorption capacity was gradually decreased with the increment of pH. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12580 Bangladesh Pharmaceutical Journal 15(2): 145-152, 2012